Relation Characteristics of Mother, ANC and Compliance of Maternity with Preeclampsia - Elok Faiqoh; Lucia Hendrati (Universitas Airlangga, 2014)
Preeclampsia is a hypertensive disorder in pregnancy which is accompanied by edema and proteinuria. This study aimed to analyze the characteristic of mothers, ANC visits, and compliance maternity care of preeclampsia in dr. Mohamad Soewandhie Surabaya. This study is using case-control with a quantitative approach. Samples are 70 people who were taken by simple random sampling method with the distribution of samples 35 cases and 35 controls. The independent variables were age, history of hypertension, history of preeclampsia, primigravida, ANC, and compliance of maternity care (provision of preeclampsia information, sources of information, advisory, and compliance to suggestions). Data analysis was performed using the Chi-Square test. The results showed that the variables are age-related (p=0.014), history of preeclampsia (p=0.000), compliance of maternity care which includes the provision of preeclampsia information (p=0.000), resources (p=0.000), provision of advice (p=0.000) and compliance of mother to advice (p=0.000). Unrelated variables is a history of hypertension (p=0.198), primigravida (p=0.791), and ANC (p=0.733). It is expected that health workers or related agencies can motivate mothers to keep up with the schedule for the next ANC examination, maintain adequate rest, and regular medication, and provide relevant health information or education about the prevention of preeclampsia.